2011
DOI: 10.1002/jccs.201190067
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐functionalized Heteroporphyrin Building Blocks and Unsymmetrical Covalent and Non‐covalent Porphyrin Dyads

Abstract: Heteroporphyrins resulted from the replacement of one or two pyrrolic nitrogens with other hetero atoms such as O, S, Se and Te possess very interesting and distinct properties compared to tetrapyrrolic porphyrins. Specially, the singlet state energy levels can be fine tuned with suitable modification of porphyrin core by substituting pyrrolic "N" with other hetero atoms such as "O" and "S". In this review, we describe our synthetic approaches for the synthesis of various mono-functionalized heteroporphyrin bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 58 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…These results and the previous data reported in hydrazones derived from chalcones [1,2,23,24,25,26,27] showed that the substituent (G) attached to the hydrazono NH function (C=N–NH–G) plays a crucial role in changing reaction pathways and reaction products. For example, when G = aroyl group, cyclization occurs in the presence of acetic anhydride to give 1,3,4-oxadiazoles [1,23,24,25,26].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These results and the previous data reported in hydrazones derived from chalcones [1,2,23,24,25,26,27] showed that the substituent (G) attached to the hydrazono NH function (C=N–NH–G) plays a crucial role in changing reaction pathways and reaction products. For example, when G = aroyl group, cyclization occurs in the presence of acetic anhydride to give 1,3,4-oxadiazoles [1,23,24,25,26].…”
Section: Resultssupporting
confidence: 87%
“…For example, when G = aroyl group, cyclization occurs in the presence of acetic anhydride to give 1,3,4-oxadiazoles [1,23,24,25,26]. On the other hand, when G = carboxamide or aryl group, cyclization with acetic anhydride gave exclusive formation of pyrazole derivatives [2,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…For example, core-modified porphyrins such as 21-thiaporphyrins have an ability to stabilize metals in oxidation states such as copper and nickel in +1 oxidation state, which is unusual for regular porphyrins . The core-modified porphyrins absorb and emit light at lower energy depending on number of heteroatoms substituted and thus can act as good energy acceptors upon covalent or noncovalent linking with regular porphyrins, which act as energy donors. Although the first heteroatom(s)-substituted porphyrins were synthesized in the 1970s, the chemistry of core-modified porphyrins evolved over the years and many new heteroatom-substituted porphyrinoids such as heterocorroles, heterochlorins, confused heteroporphyrins, and heterocarbaporphyrins were synthesized and their properties have been explored . Furthermore, the properties of core-modified porphyrins were also fine-tuned by introducing different substituents at the periphery, both at β- and meso-positions. The coordination chemistry of heteroporphyrins, which is very unique and interesting, has also been continuously exploited .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the properties of core-modified porphyrins were also fine-tuned by introducing different substituents at the periphery, both at β- and meso-positions. The coordination chemistry of heteroporphyrins, which is very unique and interesting, has also been continuously exploited . Several covalently and noncovalently linked porphyrin arrays containing heteroporphyrins as one of the components were synthesized, and their energy/electron-transfer properties have been studied. Thus, core-modified porphyrins are now comparatively better studied porphyrin analogues and can be used as substitutes for regular porphyrins and their derivatives for various applications. There are few reviews on the chemistry of core-modified porphyrins in which Latos-Grażyński et al, ,, we, ,, and others contributed by discussing the synthesis, metalation, and properties of heteroatom-substituted porphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Karami and co-workers 48 have been developed high yielding synthesis of quinoxalines and phenazines by the condensation of 1,2-dicarbonyl compounds and ortho-phenylenediamines in the presence of tungstate sulfuric acid (TSA) without the use of any solvent (Scheme 19). All reactions were performed at ambient temperature.…”
Section: Synthesis Of Polycyclic Aromatic Phenazines and Quinoxalinesmentioning
confidence: 99%